Ipsilateral fracture dislocation of the shoulder and elbow: A case report and literature review - Behr, Ian (Elsevier, 2013)
Ipsilateral dislocation of the shoulder and elbow is an uncommon injury. A literature review identified nine previously described cases. We are reporting a unique case of ipsilateral posterior shoulder dislocation and anterior elbow dislocation along with concomitant intra-articular fractures of both joints. This is the first report describing this combination of injuries. Successful treatment generally occurs with closed reduction of ipsilateral shoulder and elbow dislocations, usually reducing the elbow first. When combined with a fracture at one or both locations, closed reduction of the dislocations in conjunction with appropriate fracture management can result in a positive functional outcome.